Glucose Abnormalities Associated to Prolactin Secreting Pituitary Adenomas - Auriemma, Renata S.; De Alcubierre, Dario; Pirchio, Rosa; Pivonello, Rosario; Colao, Annamaria (Frontiers in Endocrinology, 2019)
The pathogenesis of obesity and alterations in glucose profile have been linked to PRL excess, as it is reportedly associated with metabolic syndrome in thereabout one third of patients. In vitro exposure of pancreatic islet to PRL is known to stimulate insulin secretion and β-cell proliferation, and in turn overexpression of PRL in β-cells increases insulin release and β-cell replication. PRL excess has been found to worsen glucose profile because it reduces glucose tolerance and induces insulin resistance either in obese and non-obese patients. To note, pancreatic β-cells and adipocytes widely express dopamine receptors type 2, and dopamine has been hypothesized to play a key role as modulator of insulin and adipose functions. The dopamine agonists bromocriptine and cabergoline significantly improve abnormalities in glucose profile and reduce the prevalence of metabolic syndrome in a remarkable proportion of patients, regardless of whether body weight and PRL status may change. However, in men with hyperprolactinemia complicated by hypogonadism, testosterone replacement can ameliorate insulin resistance and abnormalities in glucose metabolism. Therefore, in patients with PRL-secreting pituitary adenomas control of PRL excess by dopamine agonists is mandatory to improve glucose and insulin abnormalities.